Slope stability monitoring from microseismic field using polarization methodology; Natural Hazards and Earth System Sciences (NHESS); Vol. 3, iss. 6 - Kolesnikov Yu. I.; Nemirovich-Danchenko M. M. Mikhail Mikhailovich; Goldin S. V.; Seleznev V. S. (2003, 2003)
Title screen